Managing the Service Provider Employee and his Role in Determining the Level of Perceived Service Quality - الكيخيا فيصل (Dirasat in Economics and Business, 2013)
The service provider employee plays an important and fundamental role in improving the quality of the perceived service, from the perspective of the great impact it has on customer judgment on the quality of service provided. This is because the service provider, especially the front line employee, may the only one deals with the customer and his actions reflects the comprehensive image of the service organization, therefore a large part of the customer's judgment on the quality of service, depends to a large extent on the efficiency and ability of this employee. This paper aimed to identify the factors that control the process of managing the service providers in the service organizations to find out the most impoItant aspects related to the management of the service provider. The paper reached a set of contents and indications, which the management of the service organization should focus on them in the management of staff service providers, in order to achieve both excellence in the delivery of services, and to reach the satisfaction of the customer on the quality of service provided.